Mexico Financial Sector Assessment Program Update : Technical Note on Observance with the Core Principles for Systemically Important Payment Systems (CPSIPS): An Update - World Bank (Washington, DC : World Bank, 2022)
Financial System Assessment Program (FSAP) update mission to Mexico from February 22 to March 8, 2006, an update of the observance of the CPSS Core Principles for Systemically Important Payment Systems (CPSIPS) was carried out. The Mexican authorities provided the FSAP team with a note in which they explained how they have given follow up to the recommendations made during the FSAP of 2001 and the way the risks in the payment infrastructure, as indicated by the FSAP team, were eliminated. The update of 2006 focused on the assessment of the measures taken and no new assessments were carried out. The International Monetary Fund and the World Bank will be available to carry out full reassessments once self-assessments for the new payment system Sistema de Pagos Electrónicos Interbancarios, modern hybrid system operated by BOM (SPEI) and self-assessments of observance of the standards set by the Committee on Payment and Settlement Systems / International Organization of Securities Commissions (CPSS/IOSCO) for securities settlement systems and for central counter parties are prepared by the authorities.